El derecho de resistencia como mecanismo de control ante el uso desmedido o abuso del ius variandi. - Pacheco Castro, Jorge Luis (2016)
This paper seeks to address the problem and need that revolves around the absence and poorly interpreted regulation of the right of resistance, from the presentation of components and premises allowing you to elucidate the causes and consequences of the gap between workers and employers, as well as the serious effects that generates its so-called judicial assistance; which, we start in the first place, of the marked vertical legal relationship that exists between the labor parties, from the perspective of their rights and work-related duties, with considerable emphasis on the so-called duty of obedience. Then, in a second part, us will stop to analyze in the nature and consequences of the rule called “solve et repete” (comply, and then claim), which comes being applied unduly by them judges labour in seeks of solve a conflict that not makes rather than framing it verticality hierarchical between them parts involved in a relationship of work. In the third part of the present research, will explore them criteria established by our Court constitutional, which as maximum interpreter of the Constitution, seeks to unravel and evaluate a possible weighting between them subject of the relationship legal labor; i.e., ponder to the duty of obedience vs. the right to resist the business orders, with the aim of both subjects reaching almost perfect and equitable legal security. On the other hand, in the fourth chapter, we will understand how the so-called exercise of “ius variandi”, their limits and possible abuses, as well as the little protection provided by our legislation the worker involved, given that in certain cases, irregular exercise or abuse of the power of direction can cause compliance or improper observance of business provisions that could cause undesirable situations and even injury to the dignity and other fundamental worker rights who for fear of being penalized, to observe without objection the instructive anomalous business. The last chapter deals with the right of resistance, whose scarce and almost zero treatment in legislation, jurisprudence and doctrine Peruvian, attracts even more my academic interest. This reason that the right of resistance acquired efficiency within the framework of a process labor and/or constitutional, especially in the first under the new regulation of those. Also talk about those cases in which the contempt is justification in the reason of the instructive or in the protection of a fundamental right. On the other hand, will teach them alternative proceduralthat the affected in its right of resistance would have on hand so the injury can get an effective jurisdictional protection. Finally, after all this expanded approach, accurate my interest in showing a new perspective on the right of resistance, in order to help reduce the marked disparity in a working relationship, both the procedural path as substantive, to allow that protection to attend different criteria covered in the present report. It is not more to remember that labour law must operate, today more than ever, in a harmonious way in the framework of a social, democratic State and law as our. This is the North pursued this thesis.